Case report: Moderate therapeutic response to Bevacizumab in late-onset Labrune syndrome - Wang, Meiping; Lu, Jinmei; Wang, Xiaoxi; Ba, Xiaoqun; Wu, Dengchang; Zhang, Jianfang; Zhou, Jiajia; Wang, Kang (Frontiers in Neurology, 2022)
Labrune syndrome (LS) is caused by SNORD118 gene mutations with a particular neuroimaging of white matter disease, intracranial calcification, and cysts. There was no effective treatment until now. An 18-year-old man with infancy-onset LS was first treated with vascular endothelial growth factor (VEGF) inhibitor Bevacizumab for 1 year, resulting in significant clinical and radiological improvements. We adopted a similar regimen in a patient with late-onset LS and demonstrated moderate cognitive improvements but without changes in imaging. As such, Bevacizumab could potentially be clinically effective in adult-onset LS with great safety.